THE EFFECT OF HERRINGBONE TECHNIQUE ON THE STUDENTS’ ABILITY IN READING COMPREHENSION ON RECOUNT TEXT - Sam Roberto Andre Hasian Lumbantobing; Hilman Pardede; Herman herman (STKIP Persada Khatulistiwa Sintang, 2020)
This research is a study of improving students’ ability in reading comprehension. The aim was to find out whether the use of Herringbone technique would bring a significant difference in teaching reading comprehension through Recount text, compared with the result before the students being treated. The study was conducted in the tenth grade students of SMA N 4 Pematangsiantar. The research method used was the experimental design, where the Experimental group was the PMIA 3 class, and the PMIA 2 class as the control class. Both of the classes had 34 students in each of it. The data were obtained through pre-test, treatment and post test. The pre-test was held to know the students’ basic ability or score before treatment was given. Meanwhile, the post test was held to know the students’ achievement and significant effect after the students were taught using Herringbone technique. Finding of the research showed that both groups had a significant improvement in their reading ability after being treated and passed the KKM. The Control group, which the pre-test score was 60, made an improvement shown in their post-test score in amount of 70,44. The experimental group, the group which the researcher treated the Herringbone technique to them, had a higher improvement than the control group. The average score of pre-test in this group was about 54,41 where then being improved up to 78,97. The score of t-test (3,981) was higher than t-table (1,668) at the level of significance 5% for two tailed test, so Null Hypothesis is rejected and Alternative Hypothesis is accepted.